Health Workers' Anxiety Experience Against Dengue Hemorrhagic Fever During Rainy Season: A Phenomenological Study - Budi Joko Santosa; Budi Yulianto; Nurlailis Saadah; Sulikah Sulikah; Tinuk Esti Handayani; Syaifoel Hardy (Universitas Aisyah Pringsewu, 2023)
Dengue Hemorrhagic Fever (DHF) is still a health problem and a severe threat in some areas of Indonesia. This disease not only has an impact on the health sector, the social sector, and the community's economy but also anxiety for health workers during the rainy season. The objective is to find out the anxiety experienced by health workers regarding DHF during the rainy season, the causal factors, and how to anticipate them. The method was a phenomenological approach with descriptive analysis. The stages include bracketing, intuitive, analyzing, and describing. The research was conducted during the rainy season in December 2022. Five informants were randomly selected to represent the regions of Aceh, West Java, East Java, Flores, South Maluku, and Papua. Primary data were obtained from semi-structured interviews with four. Secondary data were obtained from official documents and reputable journals for the last five years. The data were processed using phenomenology (bracketing, intuitive, analyzing, and describing) and descriptively analyzed. Results show healthcare workers experience anxiety that can potentially arise due to changing seasons during the rainy season (18.75%), the dynamics of government regulations against DHF (31.25%), increased workload especially during the Covid-19 pandemic (31.25%), and the location of the place work (18.75%). Program enrichment in the form of debriefing training in dealing with DHF for healthcare workers in case-prone places needs to emphasize helping psychological and mental readiness so that it can reduce the level of anxiety when there is a change in weather which is followed by an increase in the incidence rate of DHF. Abstrak: Dengue Hemorrhagic Fever (DHF) masih menjadi masalah kesehatan dan ancaman serius di sejumlah wilayah di Indonesia. Penyakit ini tidak hanya berdampak terhadap sektor kesehatan, sektor sosial dan ekonomi masyarakat, namun juga terhadap kecemasan bagi petugas kesehatan. Tujuannya untuk mengetahui sejauh mana kecemasan petugas kesehatan terhadap DHF selama musim penghujan, faktor penyebab serta bagaimana mengantisipasinya. Pendekatan penelitian ini fenomenologi dengan analisis descriptive. Tahapannya mencakup bracketing, intuiting, analyzing, dan describing. Penelitian dilakukan selama musim hujan bulan Desember 2022. Lima informan dalam penelitian ini dipilih secara random untuk mewakili wilayah Aceh, Jawa Barat, Jawa Timur, Flores, Maluku Selatan dan Papua. Data primer diperoleh dari hasil interview semi struktur dengan empat tema. Data sekunder diperoleh dari dokumen resmi dan jurnal bereputasi selama lima tahun terakhir. Olah data menggunakan fenomenologi (bracketing, intuiting, analyzing and describing) dan dianalisis secara descriptive. Hasilnya petugas mengalami kecemasan yang secara potensial bisa timbul karena adanya perubahan musim khususnya pada musim hujan (18.75%), dinamika aturan pemerintah terhadap DHF (31.25%), peningkatan beban kerja khususnya selama pandemic Covid-19 (31.25%), dan lokasi tempat kerja (18.75%). Kesimpulannya pengkayaan program berupa pelatihan pembekalan dalam menghadapi DHF bagi healthcare workers di tempat yang rawan kasus perlu penekanan dalam membantu kesiapan mental psikologis sehingga bisa mengurangi tingkat anxiety ketika terjadi perubahan cuaca yang diikuti meningkatnya incidence rate DHF